Interleukin 23 Produced by Hepatic Monocyte-Derived Macrophages Is Essential for the Development of Murine Primary Biliary Cholangitis - Reuveni, Debby; Brezis, Miriam R.; Brazowski, Eli; Vinestock, Philip; Leung, Patrick S. C.; Thakker, Paresh; Gershwin, M. Eric; Zigmond, Ehud (Frontiers in Immunology, 2021)
Background and Aims: Primary Biliary Cholangitis (PBC) is an organ-specific autoimmune liver disease. Mononuclear phagocytes (MNPs), comprise of monocyte, dendritic cells and monocyte-derived macrophages, constitute major arm of the innate immune system known to be involved in the pathogenesis of autoimmune disorders. MNPs were shown to accumulate around intra-hepatic bile ducts in livers of PBC patients. Interleukin 23 (IL-23) is a pro-inflammatory cytokine. IL-23-positive cells were detected in livers of patients with advanced stage PBC and IL-23 serum levels found to be in correlation with PBC disease severity. Our overall goal was to assess the importance of IL-23 derived from MNPs in PBC pathogenesis. Methods: We utilized an inducible murine model of PBC and took advantage of transgenic mice targeting expression of IL-23 by specific MNP populations. Analysis included liver histology assessment, flow cytometry of hepatic immune cells and hepatic cytokine profile evaluation. Specific MNPs sub-populations were sorted and assessed for IL-23 expression levels. Results: Flow cytometry analysis of non-parenchymal liver cells in autoimmune cholangitis revealed massive infiltration of the liver by MNPs and neutrophils and a decrease in Kupffer cells numbers. In addition, a 4-fold increase in the incidence of hepatic IL-17A producing CD4+ T cells was found to be associated with an increase in hepatic IL23-p19 and IL17A expression levels. Disease severity was significantly ameliorated in both CD11ccreP19flox/flox and CX3CR1creP19 flox/flox mice as assessed by reduced portal inflammation and decreased hepatic expression of various inflammatory cytokines. Amelioration of disease severity was associated with reduction in IL-17A producing CD4+ T cells percentages and decreased hepatic IL23-p19 and IL17A expression levels. qRT-PCR analysis of sorted hepatic MNPs demonstrated high expression levels of IL-23 mRNA specifically by CX3CR1hiCD11c+ monocyte-derived macrophages. Conclusion: Our results indicate a major role for IL-23 produced by hepatic monocyte-derived macrophages in the pathogenesis of PBC. These results may pave the road for the development of new immune-based and cell specific therapeutic modalities for PBC patients not responding to current therapies.